Kindle fire application sketch book - Kaplan, Dean (Apress, 2011)
Think you have the next great Kindle Fire app idea? The Kindle Fire Application Sketch Book is an essential tool for any aspiring Kindle Fire developer. This sketch book makes it easy to centralize and organize your ideas, featuring enlarged Kindle Fire templates to write on. Professionally printed on high-quality paper, it has a total of 150 gridded templates for you to draft ideas and doodle designs while providing ample room to make notes and document the app name and screen name. This book is an invaluable tool for bringing your next great Kindle Fire app idea to lif